Gamifikasi Pendidikan: Ketika Belajar Menjadi Sebuah Petualangan - Nina Gantina (Jurnal Pendidikan dan Sastra Inggris, 2025)
Gamification has become a new approach in education that offers a more interactive and enjoyable learning experience. The challenge of maintaining students' motivation to learn encourages educators to look for alternative methods that are more in line with the characteristics of today's digital generation. Gamification is present as a potential solution to overcome boredom in the traditional learning process. This study aims to analyze the effectiveness of gamification-based learning methods in improving student learning outcomes and motivation. The study used a quantitative approach with a quasi-experimental design involving an experimental group and a control group. The research instrument consisted of a learning outcome test and a learning motivation questionnaire. Data analysis was carried out by normality, homogeneity, independent sample t-test, and paired sample t-test. The research sample was taken from junior high school students with a total of 60 participants who were divided equally into two groups. The results of the study showed a significant improvement in student learning outcomes and motivation after the implementation of gamification. The experimental group showed higher posttest scores and motivation scores than the control group. Gamification-based learning has proven to be effective in creating a more engaging and productive learning atmosphere. This study concludes that gamification is not only able to improve academic achievement, but also strengthen students' emotional involvement in the learning process. These findings serve as a conceptual and practical basis for the development of future learning strategies that are more adaptive and responsive to the times.